(untitled) (Research, Society and Development, 2022)
There are several variables that influence the mining production process, in order to achieve better and better results, much is done using performance indicators. This work aims to identify the main performance indicators used in mining, these separated by areas such as production, human and environmental factors. The study was based on an extensive search for scientific publications, considering the period from 2010 to 2021. The results showed that the number of academic publications related to the performance indicators found in the 3 proposed areas showed similar growth. There is a greater evolution in the number of publications related to human factors, compared to other sectors, demonstrating a concern on the part of mining companies, especially with the safety of their workers. It was concluded that events in mining, such as accidents involving tailings dams, and the mining economic scenario, such as the variation in the value of iron ore in the world, were factors that influenced the behavior of the number of scientific publications referring to performance indicators found in mining.